Seed Yield and Quality as Influenced by Plant Growth Regulators and Stages of Spray in Bitter Gourd cv. Coimbatore Long - SHANTAPPA TIRAKANNANAVAR; M. SHEKHARGOUDA; M.N. MERWADE; V. K. DESHPANDE (Seed Research, 2026)
An experiment was conducted to find out the effect of growth regulators and stages of spray on seed yield and quality in bitter gourd variety Coimbatore Long during rabi 2002-03 and 2003-04. The NAA @50 ppm sprayed at two to four leaf stage recorded maximum seed yield ha¹ (840.0kg) which, was on par with ethrel 250 ppm sprayed at two to four leaf stage (805.50kg/ha). The maximum germination percentage (87.95%), root length (19.43 cm), shoot length (12.28 cm), seedling dry weight (131.70 mg) and vigour index (2769) were recorded with NAA @ 100 ppm. Spray of growth regulators at 15 days after flower initiation recorded higher germination percentage (83.70%), shoot length (11.63 cm) and vigour index (2462) in bitter gourd.